Development Of Supersulfated Self-Consolidating Concrete Incorporating High-Volume Of Industrial By-Products - Jasme, Nurshafarina (2020)
An industrial by-product is one of the attractive alternatives to cement materials that can reduce the consumption of natural resources as well as encouraging recycling activity. One of the high-volume utilisations is by using it in supersulfated binder system. However, current limited knowledge framework established about the properties of supersulfated binder need to be addressed. Thus, this research was aims to evaluate the properties of supersulfated self-consolidating concrete (SCC) containing combination of high-volume industrial by-products namely ground granulated blast furnace slag (GGBS), fly ash with small portion of gypsum and cement. Apart from that, the granite quarry waste (GQW) was used as fine aggregate, and electric arc furnace (EAF) slag and granite stone were used as the coarse aggregates in the development of SCC. The binder composition consists of 80% GGBS and 20% fly ash was recorded as optimum percentage to be used as primary binder phase in supersulfated binder. The combination was activated with the addition of 0-10% blended OPC-gypsum. The supersulfated SCC was cured under moist curing condition and tested up to 270 curing ages. The examination of fresh, engineering, drying shrinkage, durability and microstructure properties was later conducted to develop a comprehensive knowledge framework on the properties of the supersulfated SCC. All supersulfated SCC only required water to binder (w/b) ratio of 0.27-0.33 with a fixed 0.6% of the polycarboxylate superplasticiser (SP) to achieve the desired SCC fresh properties requirement.